Cumulative disruptions: interdependency and commitment escalation as mechanisms of illicit network failure - Fabiani, Michelle D. (Global crime, 2021)
Disruptions can take many forms resulting from both internal and external tensions. How illicit networks fail to adapt to a wide range of disruptions is an important but understudied area of network analysis. Moreover, disruptions can be cumulative, constraining the possible set of subsequent adaptations for a network given previous investments. Drawing from a multi-national/multi-year investigation of a prominent Chinese human smuggling network operated by Cheng Chui Ping (‘Sister Ping’), we find that the network’s failure was a product of two interrelated factors. First, efforts to scale the network to meet increased demand made the network more interdependent, adding new members and increasing vulnerabilities to internal disruptions. Second, internal and external disruptions during a shipment cumulatively constrained the network’s ability to adapt, forcing the network to escalate their commitment rather than abandon the transit. The results suggest network disruptions should be examined holistically to improve our understanding of network failure.